1989
DOI: 10.1073/pnas.86.8.2976
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a diuretic hormone from the tobacco hornworm, Manduca sexta

Abstract: A diuretic hormone (DH) has been isolated from pharate adult heads of Manduca sexta by a nine-step purification procedure. The primary structure of the aminoterminal 40 residues was determined by sequence analysis of intact DH. The structure of an amidated carboxyl-terminal tryptic hexapeptide was characterized by sequence analysis of the peptide, and this hexapeptide was later compared by reversed-phase liquid chromatography with two synthetic hexapeptides with the free acid or amide at the carboxyl terminus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(97 citation statements)
references
References 31 publications
0
95
0
1
Order By: Relevance
“…Studies conducted primarily in insect models, where only a single CRH-like peptide (DHs) is present, suggest that the earliest function of the peptide family was associated with diuresis and feeding (Kataoka et al 1989, Audsley et al 1997, Coast 2007, 1998. Given the phylogenetic age of the CRH peptides, this is not surprising.…”
Section: Description Of Crh Family Of Peptides and Their Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted primarily in insect models, where only a single CRH-like peptide (DHs) is present, suggest that the earliest function of the peptide family was associated with diuresis and feeding (Kataoka et al 1989, Audsley et al 1997, Coast 2007, 1998. Given the phylogenetic age of the CRH peptides, this is not surprising.…”
Section: Description Of Crh Family Of Peptides and Their Functionsmentioning
confidence: 99%
“…In 1989, a peptide hormone associated with diuresis in the tobacco hornworm (Manduca sexta; Kataoka et al 1989) was characterised and showed remarkable structural similarity to the CRH peptides, notably SVG. Its high degree of residue identity indicated that it was homologous to the vertebrate CRH.…”
Section: Discovery Evolution and Function Of Crh Peptidesmentioning
confidence: 99%
“…It is a 41 residues, C-terminally amidated peptide that has 29-35% sequence identity with the vertebrate CRF family of peptides. 64) Insect DHs are produced by the median neurosecretory cells (MNC) as well as neurosecretory cells in the abdominal ganglia. Axons from these regions reach the corpora cardiaca and perisympathetic organs and other neurohemal release sites.…”
Section: Diuretic Hormones (Dh)mentioning
confidence: 99%
“…This peptide shows homology to a family of vertebrate neuropeptides, including sauvagine, corticotropin-releasing factor, and urotensin I (1). Since the isolation of Mas-DH, other peptides of related structure, which function in regulating fluid balance in insects, have been isolated from Manduca (2) and from two orthopteran genera: Locusta (3,4) and Acheta (5).…”
mentioning
confidence: 99%
“…Manduca sexta diuretic hormone (Mas-DH) is an amidated 41-amino acid peptide that was isolated from pharate adult tobacco hornworm heads on the basis of induction of fluid loss in beheaded adult cabbageworms (1). This peptide shows homology to a family of vertebrate neuropeptides, including sauvagine, corticotropin-releasing factor, and urotensin I (1).…”
mentioning
confidence: 99%